Academics’ Views on Africanisation and Decolonization of Teacher Education Curricula: A Case Study of a Selected Higher Education Institution in South Africa - Berington Zanoxolo Gobingca (E-Journal of Humanities, Arts and Social Sciences)
The purpose of the research was to assess the academics’ views on the afrikanisation and decolonisation of teacher education curricula in South African higher education institutions (HEIs). It is meant to draw their attention to redesigning the curricula which is appropriate to fit and benefit holistically the Africans and international students who are enrolled in teacher education programmes in HEIs of South Africa. A qualitative case study was conducted using face-to-face semi-structured interviews to collect data from ten purposely selected academics in the Faculty of Education of one of the South African Universities located in the Eastern Cape Province of South Africa. The thematic approach was used to analyse the collected data from the sampled academics. It emerged that there is a mismatch between the academics’ instructional and research practices in meeting the diverse learning capabilities of Africans. It is concluded that redesigning, aligning and re-structuring the HEIs’ curricula could improve the throughputs, graduation rates, and research publication competencies of Africans. The HEIs should offer an inclusive curriculum of African and international knowledge, theories and skills. Collaboration of various stakeholders, including students, instructors, University Faculty of Education advisory board, Department of Basic Education officials as employers and financial supporters, teacher unions, school principals, school governing bodies and financial sponsors to enrolled students for their university-related activities, researchers, book publishers, and other interested parties in education, is essential to developing and implementing a transformed, diverse, impactful, relevant and quality curriculum to meet the demands of the global market.